2022
DOI: 10.4018/978-1-7998-9117-8.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Digital Transformation

Abstract: Digital literature has provided significant insights into how digital transformation contributes to improving business performance. This research departs from these studies by focusing on driving factors of digital transformation and digital transformation strategies. Moreover, the authors determine the impact of digital transformation on firm performance and identify the challenges of adopting digital transformation. The results show that successful digital transformation can speed up the pace of innovation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Hence, it is logical for volunteers to gravitate away from the traditional form to the new form of volunteering. Our results support the findings of a study carried out by Bouarar et al. (2021), which revealed that “fear of COVID-19” was the strongest antecedent of intention.…”
Section: Resultssupporting
confidence: 91%
“…Hence, it is logical for volunteers to gravitate away from the traditional form to the new form of volunteering. Our results support the findings of a study carried out by Bouarar et al. (2021), which revealed that “fear of COVID-19” was the strongest antecedent of intention.…”
Section: Resultssupporting
confidence: 91%
“…Many previous studies have confirmed the high level of the perceived risk of COVID-19, especially during peak periods among different segments of society (e.g. Bouarar et al. , 2021; Tran et al.…”
Section: Resultsmentioning
confidence: 80%
“…(2017). The perceived risk of COVID-19 was measured using a scale adapted from Bae and Chang (2021) and Bouarar et al. (2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations